Contribution to differential diagnostics of granulomatous lesions in lung tissue. - Horacek, Jaroslav; Horava, Vladimir (Biomedical papers, 2002)
Etiopathogenesis of pulmonary granulomatous lesions can be very varied. Pathologists find pulmonary granulomatous lesions in autopsies frequently. Diagnostics of pulmonary granulomatous lesions is based on anamnesis data, clinical examinations and morphological changes. In some cases, especially in long-term ill patients, morphological finding remains the only way to explain the case. We provide a description of an incidental autoptic finding of chronic granulomatous lesion in lung tissue in a man aged 81. Histopathological examination proved aspired granules of maize starch. Aspired granules triggered lesion of granulomatous character. At microscopic examination vegetable particles were defined to be maize starch. Granules of maize starch, which are a part of artificial nutrition labelled Caglusal, may have caused granulomatous lesion in our case.
Keywords: Lung / Granulomatous lesion / Diagnostics